Methanolic Root Extract of Rauwolfia serpentina Benth Improves the Glycemic, Antiatherogenic, and Cardioprotective Indices in Alloxan-Induced Diabetic Mice - Muhammad Bilal Azmi; Shamim A. Qureshi (Advances in Pharmacological Sciences)
The aim of the study was to evaluate the phytochemistry and the effect of methanolic root extract (MREt) of Rauwolfia serpentina on alloxan-induced diabetic Wister male mice. Mice were divided in control (distilled water at 1 mL/kg) and alloxan-induced diabetic mice which subdivided into diabetic (distilled water at 1 mL/kg), negative (0.05% dimethyl sulfoxide at 1 mL/kg), positive (glibenclamide at 5 mg/kg) controls, and three test groups (MREt at 10, 30, and 60 mg/kg). All treatments were given orally for 14 days. Qualitatively MREt showed the presence of alkaloids, carbohydrates, flavonoids, glycosides, cardiac glycosides, phlobatannins, resins, saponins, steroids, tannins, and triterpenoids, while quantitatively extract was rich in total phenols. The flavonoids, saponins and alkaloids were also determined in root powder. MREt found effective in improving the body weights, glucose and insulin levels, insulin/glucose ratio, glycosylated and total hemoglobin in test groups as compared to diabetic control. Similarly, significantly decreased levels of total cholesterol, triglycerides, low-density lipoprotein (LDL-c), and very low-density lipoprotein (VLDL-c) cholesterols were found in test groups. Significant lipolysis with improved glycogenesis was also found in liver tissues of all test groups. ALT levels were found normal in all groups. Thus, MREt improves the glycemic, antiatherogenic, coronary risk, and cardioprotective indices in alloxan-induced diabetic mice.